Validitas Isi Instrumen TPACK pada Calon Guru Kimia menggunakan Aplikasi Model Rasch - Wahyuni Tri Lestari; Dwi Maryani Rispatiningsih (PT. Penerbit Tiga Mutiara, 2023)
This research aims to assess the content validity of the instrument used to measure Technological Pedagogical Content Knowledge (TPACK) in prospective chemistry teachers. The evaluation encompasses a thorough analysis of the instrument's alignment with the knowledge domains being measured, ensuring that the instrument covers key aspects of TPACK that are relevant to the context of teaching chemistry. Content validity reflects the representation and relevance of a set of items used to measure a concept carried out through rational analysis of the contents of the test through an expert panel assessment. This validity refers to the accuracy of the measurement based on the contents of the instrument to ensure that the scale of the items used has fulfilled the entire concept of the item or the suitability of the item. The instrument used in this study was assessed by nine validators consisting of two chemistry education experts and seven chemistry teachers. The assessment is done by determining the appropriateness or relevance of the test contents to be used through rational analysis by a competent panel or through expert judgment. The instrument validations in this study were 20 multiple choice questions. The assessment is done by giving a score of 1-4 on each item. This research is a quantitative descriptive study using Rasch model analysis. The analysis showed that the exact agreement was 71.4% and the expected agreement was 73.8%. Based on measurements showing relevant items in this research instrument, there are 17, among others number 1, 10, 11, 14, 5, 8, 19, 20, 18, 3, 6, 12, 13, 15, 17, 4 and 9. While there are 3 items that are irrelevant and need to be corrected, including number 16, 2 and 7.